2007
DOI: 10.1080/14786430701589343
|View full text |Cite
|
Sign up to set email alerts
|

On the uniqueness and sensitivity issues in determining the elastic and plastic properties of power-law hardening materials through sharp and spherical indentation

Abstract: A systematic study of the uniqueness, reversibility and sensitivity issues associated with seven indentation-based methods of property extraction demonstrates that: (i) The indentation algorithms generally identify the elastic and plastic properties of materials uniquely for most materials. (ii) The indentation forward algorithms (wherein the indention responses are determined from the elastic and plastic properties of the indented materials) and the reverse algorithms (wherein the elastic and the plastic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…The sensitivity issues on the indentation tests are quite important and critical, and many studies have performed to examine the robustness of the developed methods (Capehart and Cheng, 2003;Prchlik, 2004;Lee et al, 2005;Lan and Venkatesh, 2007;Ge et al, 2009). We found that for our shallow spherical indentation tests (Lee et al, 2005), the sensitivity of estimated properties to variations in the load was negligible, however, as shown in Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The sensitivity issues on the indentation tests are quite important and critical, and many studies have performed to examine the robustness of the developed methods (Capehart and Cheng, 2003;Prchlik, 2004;Lee et al, 2005;Lan and Venkatesh, 2007;Ge et al, 2009). We found that for our shallow spherical indentation tests (Lee et al, 2005), the sensitivity of estimated properties to variations in the load was negligible, however, as shown in Fig.…”
Section: Discussionmentioning
confidence: 80%
“…If we could not solve the each problem one by one, we could not get the proper results. For example, Lan and Venkatesh (2007) have studied the uniqueness and sensitivity issues for power law hardening materials. However, it can be another problem if we consider actual material properties not obeying powerlaw hardening relation well, and use actual experimental indentation data containing lots of uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for such significant errors in the yield stress and strain hardening exponent values are linked to the high sensitivity of these parameters to the uncertainties in the indentation response parameters. 23,24 We thus study how the inverse method can improve the identification of these parameters.…”
Section: B Estimation Of the Starting Parametersmentioning
confidence: 99%
“…[15][16][17][18][19][20] Reviews of the existing models have been published by Capehart and Cheng 21 and by Gouldstone et al 22 To increase the robustness of the semi-analytical approach presented here, multiple input data sets have been coupled, 10,11 and recently in-depth sensitivity analysis has been performed to determine the sensitivity and robustness of the results. [23][24] The inverse method developed consists of fitting a constitutive law to a set of input data (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…the same load (P) vs penetration (h) curve. In consequence, several aspects related to the uniqueness of the solution provided by inverse methods were discussed by different authors [7][8][9][10][11][12]. For example, Mata et al [14] developed mathematical formulations to relate the hardness and pile-up or sinking-in phenomenon around sharp indentations with the elastic-plastic mechanical properties by using the results retrieved from instrumented indentation test and atomic force microscopy (from now on "methodology A").…”
Section: Introductionmentioning
confidence: 99%